Teologi Kesetiaan Allah Berdasarkan Kitab Yosua - Fati Aro Zega (THRONOS: Jurnal Teologi Kristen, 2021)
Looking at the current number of Christian life, especially the pandemic that is endemic. So the issue of loyalty becomes a new concern. Is the doctrine of faithfulness still firmly engraved as before, or has there been disturbance or disruption of the faithful's loyalty to their beliefs or loyalty to service, especially loyalty to God. The author describes God's faithfulness in the context of the book of Joshua as a concern for today's believers. By using descriptive qualitative method, in a literature study approach, it can be concluded that the problem in the book of Joshua is not a prophetic book. This book is more historical. But this Book has important theological value both for Israel and for the Church. The inheritance of the Land of Canaan is not only a theological and literal issue for Israel in the past and present, but also a symbolic issue for the Church futurist. The region of Canaanite heredity became a symbol of Christian hope, both spiritually and eschatologically. Thus this paper explains that the Lord God who is worshiped in the name of Jesus Christ is faithful. God is faithful in overcoming every situation and condition of His people no matter how difficult it is. AbstrakMelihat banyaknya kehidupan kekristenan saat ini terlebih adanya pandemi yang mewabah. Maka persoalan terhadap kesetiaan menjadi keprihatinan baru. Apakah ajaran tentang kesetiaan masih kokoh terpatri seperti semula, atau sudah mulai terjadi gangguan atau mendisrupsi kesetian orang beriman terhadap keyakinannya atau kesetiaan kepada pelayanan, utamanya kesetiaan kepada Tuhan. Penulis  mendeskripsikan kesetiaan Allah dalam kontek kitab Yosua menjadi perhatian bagi orang percaya masa kini. Dengan menggunakan metode kualitatif deskrtip, dalam pendekataan studi literature dapat disimpulkan bahwa persoalan di Kitab Yosua bukanlah kitab kenabian. Kitab ini lebih bersifat sejarah. Namun Kitab ini memiliki nilai teologi yang penting baik untuk Israel maupun untuk Gereja. Pewarisan Tanah Kanaan bukan hanya merupakan isu teologis dan literal bagi Israel pada masa lalu dan kini, tetapi juga isu simbolis bagi Gereja secara futuris. Wilayah hereditas Kanaan menjadi suatu lambang pengharapan Kristen, baik secara rohaniah maupun eskatologikal. Dengan demikian tulisan ini menjelaskan bahwa Tuhan Allah yang disembah di dalam nama Yesus Kristus adalah setia. Tuhan setia mengatasi setiap situasi dan kondisi umat-Nya sesulit apa pun.